2018
DOI: 10.3390/molecules23040774
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Toxoplasma gondii and Antimicrobial Activity of Amides Derived from Cinnamic Acid

Abstract: Most cinnamic acids, their esters, amides, aldehydes, and alcohols present several therapeutic actions through anti-inflammatory, antitumor, and inhibitory activity against a great variety of microorganisms. In this work, eight amines derived from cinnamic acid were synthesized and tested against host cells infected with Toxoplasma gondii and the bacteria Escherichia coli, Pseudomonas aeruginosa, Staphylococcus epidermidis, and three strains of Staphylococcus aureus. Compounds 3 and 4 showed the best result ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Cinnamic acid (3-phenylacrylic acid) is one kind of phenolic acid widely present in plants, which can be used in avoring materials and skin care products. [1][2][3] However, the high melting point (133 C) and poor solubility of cinnamic acid limit its application. Benzyl cinnamate (melting point 34.5 C), one of the derivatives of cinnamic acid, was oen used as a avoring agent and antioxidant in the food, cosmetic and medicine industries.…”
Section: Introductionmentioning
confidence: 99%
“…Cinnamic acid (3-phenylacrylic acid) is one kind of phenolic acid widely present in plants, which can be used in avoring materials and skin care products. [1][2][3] However, the high melting point (133 C) and poor solubility of cinnamic acid limit its application. Benzyl cinnamate (melting point 34.5 C), one of the derivatives of cinnamic acid, was oen used as a avoring agent and antioxidant in the food, cosmetic and medicine industries.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this work conveyed the disclosure of CAD as inhibitors of the new permeability pathways (NPP) induced by Plasmodium in erythrocytes to enable the translocation of carbohydrates and amino acids [46][47][48][49]. Following this pioneering discovery, other authors have proposed different CA-inspired compounds as potential therapeutic agents against malaria [26,28,29], as well as other parasitic diseases [50][51][52]. In view of this, reports have emerged over the past decade where conjugation to CA was proposed as a useful strategy for the rescuing of known antimalarials [53][54][55].…”
Section: Cinnamic Acid Conjugation In the Rescuing Of Classical Antimmentioning
confidence: 99%
“…Molecules 2020, 24, x FOR PEER REVIEW 3 of 15 malaria [26,28,29], as well as other parasitic diseases [50][51][52]. In view of this, reports have emerged over the past decade where conjugation to CA was proposed as a useful strategy for the rescuing of known antimalarials [53][54][55].…”
Section: Cinnamic Acid Conjugation In the Rescuing Of Classical Antimmentioning
confidence: 99%
“…However, existing drugs are widely vulnerable to drug-resistance in clinics globally. To overcome pharmacological barriers to these challenges, the efforts for treating infectious diseases have been attempted in various fields, and it has been reported that various extracts/compounds derived from medicinal plants and new synthetic compounds have anti- T. gondii effects in the in vitro and pre-clinic stages [10,11,12,13,14,15]. Until recently, various compounds derived from plants have showed a leading role and ability as a source of specialized metabolites with medical effects as well as pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%